2007
DOI: 10.1177/0269881107067097
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic psychotomimetic phencyclidine induces deficits in reversal learning and alterations in parvalbumin-immunoreactive expression in the rat

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
127
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(140 citation statements)
references
References 61 publications
11
127
0
2
Order By: Relevance
“…Certainly, no one animal protocol can effectively model a disease as complex and heterogeneous as schizophrenia, and previous reports (Pantelis et al, 1999) suggest that individuals with schizophrenia can demonstrate impairment on multiple aspects of cognition, including some non-EDS problems, an effect not addressed by our rodent model. However, the face validity of our model is augmented by previous reports of schizophrenia-like pathology, such as decreased parvalbumin expression (Abdul-Monim et al, 2007) and cortical metabolic hypofunction (Cochran et al, 2003) following PCP administration. Future research should determine whether differential pharmacological effects are replicated in another recently developed neurodevelopmental rodent model of schizophrenia, neonatal treatment with the neurotoxin MAM (methylazoxymethanol), which has been demonstrated to produce impairments in attentional set shifting (Featherstone et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Certainly, no one animal protocol can effectively model a disease as complex and heterogeneous as schizophrenia, and previous reports (Pantelis et al, 1999) suggest that individuals with schizophrenia can demonstrate impairment on multiple aspects of cognition, including some non-EDS problems, an effect not addressed by our rodent model. However, the face validity of our model is augmented by previous reports of schizophrenia-like pathology, such as decreased parvalbumin expression (Abdul-Monim et al, 2007) and cortical metabolic hypofunction (Cochran et al, 2003) following PCP administration. Future research should determine whether differential pharmacological effects are replicated in another recently developed neurodevelopmental rodent model of schizophrenia, neonatal treatment with the neurotoxin MAM (methylazoxymethanol), which has been demonstrated to produce impairments in attentional set shifting (Featherstone et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, although cortical disinhibition could disrupt basic object memory processing, it might be expected to have a larger impact on performance in the CMOR task, which likely relies on even greater integration of information processing across cortical regions. The neural effects induced by sub-chronic NMDAR antagonists are widespread (Abdul-Monim et al, 2007;Keilhoff et al, 2004;Mouri et al, 2007), and the extent to which dysfunction in various cortical and/or subcortical regions contributes to the selective CMOR deficits observed here remains to be determined. Ongoing and future studies in our lab will aim to answer these and related questions.…”
Section: Discussionmentioning
confidence: 94%
“…In our laboratory, we have shown that PCP selectively impairs performance in reversal learning (Abdul-Monim et al, 2006;McLean et al, 2009), attentional set-shifting (McLean et al, 2008a) and novel object recognition (Grayson et al, 2007), importantly these tests are all of relevance to schizophrenia as highlighted by the MATRICS.ucla.edu initiative (Measurement and Treatment Research to Improve Cognition in Schizophrenia), and subsequently the TURNS.ucla.edu program (Treatment Units for Research on Neurocognition and Schizophrenia). Our sub-chronic PCP dosing regime causes reduced density of parvalbumin-immunoreactive neurons in hippocampal regions (Abdul-Monim et al, 2007) and levels of brain-derived neurotrophic factor mRNA (BDNF) in cortical regions (Snigdha et al, 2007) in rats. Reductions in GABAergic interneurones in these areas have been found in post-mortem analysis from patients with schizophrenia (Benes et al, 1991;Benes and Berretta, 2001;Beasley et al, 2002;Zhang and Reynolds, 2002).…”
Section: Introductionmentioning
confidence: 98%